1987
DOI: 10.1016/0378-5955(87)90122-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ototoxicity of gentamicin in the guinea pig and two strains of rats

Abstract: Gentamicin ototoxicity and nephrotoxicity were compared in two strains of rats, Sprague-Dawley and Fisher-344, and in the Hartley albino guinea pig. Treatment groups consisting of 8 male rats of each strain and four male guinea pigs were dosed subcutaneously for 14 days with either 80 or 100 mg/kg of gentamicin sulfate in saline. Brainstem auditory evoked response (BAER) thresholds were recorded from each animal in each group on day 11 post-administration. Blood urea-nitrogen and serum creatinine were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…This is particularly true when very early events following hair cell damage are of interest. Because systemic aminoglycoside injections in mammals are limited by toxicity, lower doses given over an extended period of time are often necessary before hair cell damage is obtained (Wu et al, 2001;Forge and Shacht, 2000;Sullivan et al, 1987). This results in gradual injury to the sensory epithelium and interferes with attempts to pinpoint the stages of cellular change in time and to study the earliest events following damage.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is particularly true when very early events following hair cell damage are of interest. Because systemic aminoglycoside injections in mammals are limited by toxicity, lower doses given over an extended period of time are often necessary before hair cell damage is obtained (Wu et al, 2001;Forge and Shacht, 2000;Sullivan et al, 1987). This results in gradual injury to the sensory epithelium and interferes with attempts to pinpoint the stages of cellular change in time and to study the earliest events following damage.…”
Section: Discussionmentioning
confidence: 98%
“…Application methods used to date have included systemic injection and local application via trans-tympanic injection, endolymphatic sac injection, and intracochlear perfusion (Sullivan et al, 1987;Kimura et al, 1988;Lee and Kimura, 1991;Wanamaker et al, 1998;Dodson, 1997). Although systemic injection has been a particularly useful application method in some species, it has limitations in the mouse.…”
Section: Introductionmentioning
confidence: 98%
“…Here, we evaluated the use of MitoQ, a mitochondriatargeted derivative of the antioxidant CoQ 10 , as a potent and novel therapeutic agent for the prevention of cochlear cell damage and hearing loss induced by the AG gentamicin, which is cochleotoxic in guinea pigs (28).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a dose of 40 mg/kg gentamicin produced nephrotoxicity in F344 rats while a dose of 70-100 mg/kg was required to induce an equivalent adverse effect in Sprague-Dawley animals, and male F344 rats were more susceptible than females to gentamicin-induced renal damage (Goodrich & Hottendorf, 1995;Sugarman et al, 1983;Kacew, 1989;Kacew & Bergeron , 1990). Sullivan et al (1987) reported that Sprague-Dawley rats were more resistant to the nephrotoxic and ototoxic effect of gentamicin than F344 animals. A decreased susceptibility to the nephrotoxic action of gentamicin in Sprague-D aw ley rats w as supported by the observation that proteinuria occurre d after 4 d in Wistar rats, whereas in Sprague-D awley animals 9-10 d was needed to produce this adverse effect (Smetana et al, 1988(Smetana et al, , 1992.…”
Section: Kidneymentioning
confidence: 94%